Variation in intraocular pressure by sex, age, and geographic location in China: A nationwide study of 284,937 adults - Liu, Xuan; Pan, Xue; Ma, Yuan; Jin, Cheng; Wang, Bo; Ning, Yi (Frontiers in Endocrinology, 2022)
Objective: To investigate the distribution characteristics of intraocular pressure (IOP) by sex, age, and geographic location in China and to build the corresponding reference intervals (RIs). Material and methods: A cross-sectional, multi-centered, population-based study was conducted. All data were collected from participants without eye diseases who underwent ophthalmological examinations in 170 Health Screening Centers in mainland China in 2018. The non-contact tonometer was used to measure IOP. The age-, sex-, and province-specific RIs of IOP were investigated. The IOP of different age–sex groups was further explored by stratifying according to height, body mass index (BMI), blood pressure, altitude, and geographic area. Results: During the study, a population-based sample of 284,937 participants was included. The distribution of measured IOP followed an approximately Gaussian distribution, with a higher mean value in men than in women. The IOP showed a general trend of decline with age for both men and women and varied across geographical locations. The mean IOP was 15.4 (95% CI: 9.1-21.6) mmHg for men and 14.9 (95% CI: 9.0-20.8) mmHg for women. For men, it decreased from 11.0-23.5 mmHg at age 18-24 years to 10.5-20.5 mmHg at age ≥70 years. For women, it decreased from 10.5-22.0 to mmHg at age 18-24 years to 10.0-21.0 mm Hg at age ≥70 years. Conclusions: The IOP varied with age, sex, metabolic disorders and geographic location. These RIs should be considered in the clinical process of glaucoma diagnosis and treatment.